La silenciosa expansion de la jurisdiccion universal - Langer, Máximo (2020)
Based on an original worldwide survey of all universal jurisdiction complaints over core international crimes presented between 1961 and 2017 and against widespread perception by international criminal law experts that universal jurisdiction is in decline, this article shows that universal jurisdiction practice has been quietly expanding as there has been a significant growth in the number of universal jurisdiction trials, in the frequency with which these trials take place year by year and in the geographical scope of universal jurisdiction litigation. This expansion is likely the result of, among other factors, the adoption of International Criminal Court implementing statutes, the creation of specialized international crimes units by states, institutional learning by states and non-governmental organizations (NGOs), technological changes, new migration and refugee waves to universal jurisdiction states, criticisms of inter- national criminal law as neo-colonial and the search of new venues by human rights NGOs. The expansion of universal jurisdiction has been quiet because most tried defendants have been low-level, universal jurisdiction states have not made an effort to publicize these trials and observers have wrongly assumed that Belgium and Spain were representative of universal jurisdiction trends. The article finally assesses positive and negative aspects of the quiet expansion of universal jurisdiction for its defenders and critics